Detecting native language group differences at the subskills level of reading: A differential skill functioning approach. (April 2013) - Li, Hongli; Suen, Hoi K
Differential skill functioning (DSF) exists when examinees from different groups have different probabilities of successful performance in a certain subskill underlying the measured construct, given that they have the same ability on the overall construct. Using a DSF approach, this study examined the differences between two native language groups – a group with an East Asian language background and one with a Romance language background – in regard to reading subskills as represented in the Michigan English Language Assessment Battery (MELAB) reading test. Based on a combination of literature review and think-aloud reports from a sample of ESL students, hypotheses on reading subskill differences between the two groups were generated. These hypotheses were tested by first identifying the subskill profile of each examinee in a large MELAB database via the application of a previously determined item-skill Q-matrix to a Fusion Model of cognitive diagnostic modeling. The subskill profiles of the East Asian examinees were then compared against those of examinees with a Romance language background through logistic regression techniques. Some important DSFs were found between the two groups. Based on results of this study, instructional strategies were suggested to address some specific weaknesses in ESL learners' reading subskills.